Impacto das notícias falsas na tomada de decisões e na percepção da população de Manaus - Alencar, Waléria Dias (Brasil, 2024)
This article investigates the impact of fake news on the perception and behavior of the population of Manaus, with the aim of analyzing how disinformation affects public opinion and influences citizens' decisions. The survey was carried out with 321 participants using an online questionnaire, and the data was analyzed statistically. The results indicate that a significant proportion of respondents are influenced by the news they consume on social media. Regarding the potential of false information to interfere in important decisions, such as voting or adherence to medical treatment, the majority agreed that this news has a major impact on these choices. The study reinforces the relationship between disinformation and political polarization, highlighting the effect of fake news in shaping opinions and behaviours, especially on issues related to politics and health. It also broadens our understanding of the social context and highlights the importance of developing effective strategies to combat disinformation, especially in sensitive areas.